Single White Looter: Have Whip, Will Travel - Champion, Erik (Sidestone Press, 2017)
This paper focuses on how generic game-based interaction could help improve the design of video games for archaeological (and heritage) purposes. I will address three questions: 1. Can we use genres to classify, evaluate, and predict the impact and success of games in archaeological research? 2.If the answer to the first question is not clear, are there common elements or features in computer games that would help us understand the difficulty of developing games for archaeology? 3. Given our understanding of these common game elements or features, could a refined theory of game mechanics help computer games convey archaeological method and archaeological interpretations?